Development and Significance of Agricultural Services in the Economy of Uzbekistan - Khalimov Sh. Kh. (Researchparks Publishing, 2022)
The article describes the role and importance of services in the developing agricultural sector of the country, the growth rates of gross domestic product and agriculture, as well as signs of improving the organizational and economic mechanisms of the service sector.